Saponin-rich fraction from Agave sisalana: effect against malignant astrocytic cells and its chemical characterisation by ESI-MS/MS. Issue 12 (18th June 2019) - de Oliveira, João Victor A.; Botura, Mariana B.; dos Santos, Jener D. G.; Argolo, Deivison S.; da Silva, Victor Diogenes A.; da Silva, Gisele D.; de Lima, Hélimar G.; Braz Filho, Raimundo; Vieira, Ivo Jose C.; Branco, Alexsandro; Batatinha, Maria José M.; Costa, Silvia L.
Abstract: Astrocytic tumour cells derived from human (GL-15) and rat (C6) gliomas, as well as non-tumoural astrocytic cells, were exposed to the saponin-rich fraction (SF) from Agave sisalana waste and the cytotoxic effects were evaluated. Cytotoxicity assays revealed a reduction of cell viability that was more intensive in glioma than in non-tumoural cells. The SF induced morphological changes in C6 cells. They were characterised by cytoplasmic vacuole formation associated with increase in the formation of acidic lysosomes. The SF was subjected to purification on Sephadex LH-20, which characterised three probable steroidal saponins (sisalins) by electrospray ionisation mass spectrometry multistage (ESI-MS n ). Sisalins from sisal may be responsible for the cytotoxicity, which involves cytoplasmatic vacuole formation and selective action for glioma cells. Abstract :